Plant Names in Constructed Worlds - Alberto Ghia (RiCognizioni)
This study investigates the extent to which plant names, coined within the context of fictional world-building, reflect the morphosyntactic and semantic-motivational structures characteristic of natural language phytonyms. The analysis begins by outlining the repertoire selection criteria, encompassing fictional worlds, sources, and methodologies for plant name identification. It then explores the strategies used to integrate plants into fictional settings, categorizing them into four distinct types based on two variables: the plant's real or fictitious nature and whether the naming language is natural or constructed (artlang). Furthermore, the study examines the alignment of invented plant names with Brent Berlin's five principles of ethnobotanical nomenclature, focusing on morphosyntactic and semantic aspects. The presence of phenomena such as synonymy and borrowing, typical of folk phytonyms repertoires, is also analyzed, offering insights into the linguistic parallels between natural and constructed ecosystems.